A Case Report of Stroke in Secondary Hyperoxaluria - Vaishnavi, Nethaji Sree; Anuradha, N.; Prabu, Viknesh; Preeti, C.D.; Sanjith, Konda (Journal of Coastal Life Medicine, 2023)
Hyperoxaluria is most common in developed countries like the USA, but not sporadic in developing countries. Hyperoxaluria is a state, that occurs when a patient has an excess of oxalate formation in urine. hyperoxaluria is of two types- Primary hyperoxaluria is due to an inherited defect of alanine glyoxalate transaminase. Secondary hyperoxaluria is due to increased GIT absorption of oxalates. In hyperoxaluria, there are increased oxalate levels in the blood, which get accumulate in joint spaces, tissues, and bone marrow resulting in systemic oxalosis. The conjunction of hyperoxaluria and CNS ischemia stroke is unusual Here we are discussing a case of 71 years old male patient with a known case of Crohn’s disease for 20 years, with a history of small bowel resection 6 years back, with an intact colon, post-operatively not on regular medications. History of recurrent renal stones, history of insomnia, presented with CNS ischemic stroke In this patient, there is an increased chance of secondary hyperoxaluria, due to raised absorbency of the large intestine to oxalates, which also increases blood oxalates levels, and there is a surge in accumulation of free oxalates in the large intestine lumen, due to fatty acids combined with luminal calcium. In patients with secondary hyper-oxalosis, that circulating oxalate precipitate could be a risk factor for stroke